2021
DOI: 10.3171/2020.10.spine201511
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of vancomycin on rat bone marrow–derived mesenchymal stem cell differentiation

Abstract: OBJECTIVE The use of intrawound vancomycin powder in spine surgery has been shown to decrease the rate of surgical site infections; however, the optimal dose is unknown. High-dose vancomycin inhibits osteoblast proliferation in vitro and may decrease the rate of solid arthrodesis. Bone marrow–derived mesenchymal stem cells (BMSCs) are multipotent cells that are a source of osteogenesis in spine fusions. The purpose of this study was to determine the effects of vancomycin on rat BMSC viability and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The present results indicated that BMSCs and ADSCs differentiated toward an NPC-like phenotype, and that ADSCs had a greater ability to differentiate into NPC-like cells than BMSCs. Previous studies demonstrated that both BMSCs ( 53 , 58 ) and ADSCs ( 27 ) could differentiate toward NPC-like cells under the same conditions with a differentiating medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results indicated that BMSCs and ADSCs differentiated toward an NPC-like phenotype, and that ADSCs had a greater ability to differentiate into NPC-like cells than BMSCs. Previous studies demonstrated that both BMSCs ( 53 , 58 ) and ADSCs ( 27 ) could differentiate toward NPC-like cells under the same conditions with a differentiating medium.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of BMSCs and ADSCs. BMSCs were isolated and purified using the whole bone marrow cell repeated adherent culture method (27)(28)(29)(30). All animal experiments were approved by the Animal Experiment and Ethics Committee of Kunming Medical University (Kunming, China; approval no.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Hanson et al 15 demonstrated that exposure of rat bone marrow–derived mesenchymal stem cells to 4000 µg/mL vancomycin for 4 days reduced cell viability by >60% and impaired calcium deposition. Braun et al 5 determined that only vancomycin concentrations >1000 µg/mL will decrease cell viability and ALP activity in human osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is reported that antibiotic treatment controls infection, it inhibits the osteoblast proliferation and viability, resulting in poor bone regeneration. 71,72 Several AMPs are identified with the capability to differentiate MSCs to osteoblast and to facilitate bone repair. Li et al proposed that AMPs activate transcription of bone morphogenetic protein-2 (BMP-2), which further activates SMAD1/5/8 and mitogen-activated protein (MAP) kinase pathways, leading to phosphorylation of SMAD1/5/8 proteins.…”
Section: Bone Regeneration Mechanismsmentioning
confidence: 99%